Evaluating the impact of the genitourinary multidisciplinary tumour board: Should every cancer patient be discussed as standard of care? - Scarberry, Kyle; Ponsky, Lee; Cherullo, Edward; Larchian, William; Bodner, Donald; Cooney, Matthew; Ellis, Rodney; MacLennan, Gregory; Johnson, Ben; Tabayoyong, William; Abouassaly, Robert (Canadian Urological Association Journal, 2018)
Introduction: We sought to prospectively evaluate the effectiveness of the multidisciplinary tumour board (MTB) on altering treatment plans for genitourinary (GU) cancer patients. Methods: All GU cancer patients seen at our tertiary care hospital are discussed at MTB. We prospectively collected data on adult patients discussed over a continuous, 20-month period. Physicians completed a survey prior to MTB to document their opinion on the likelihood of change in their patient’s treatment plan. Logistic regression was used to asses for factors associated with a change by the MTB, including patient age or sex, malignancy type, the predicted treatment plan, and the provider’s years of experience or fellowship training. Results: A total of 321 cancer patients were included. Patients were primarily male (84.4%) with a median age of 67 years old (range 20–92). Prostate (38.9%), bladder (31.8%), and kidney cancer (19.6%) were the most common malignancies discussed. A change in management plan following MTB was observed in 57 (17.8%) patients. The physician predicted a likely change in six (10.5%) of these patients. Multivariate logistic regression did not determine physician prediction to be associated with treatment plan change, and the only significant variable identified was a plan to discuss multiple treatment options with a patient (odds ratio 2.46; 95% confidence interval 1.09–9.54). Conclusions: Routine discussion of all urologic oncology cases at MTB led to a change in treatment plan in 17.8% of patients. Physicians cannot reliably predict which patients have their treatment plan altered. Selectively choosing patients to be presented likely undervalues the impact of a multidisciplinary approach to care.